Pembuatan Bee Polen Dalam Upaya Pengembangan Usaha Lebah Kelulut (Trigona sp) Di Hutan Kampus Universitas Palangka Raya : Production of Bee Pollen in an Effort to Develop The Kelulut Bee (Trigona sp) Business in The Foresto of The Palangka Raya University Campus - Nuwa, Nuwa; Rotinsulu, Johanna Maria; Triyadi, Antonius (HUTAN TROPIKA, 2025)
Trigona spp. is a species of bee that has a unique characteristic: it does not have a stinger, making it easy to cultivate. This type of bee is widely cultivated in Indonesia. The cultivation of Kelulut honey bees can provide direct benefits through the utilization of products produced by honey bees, such as honey, royal jelly, bee pollen, wax, propolis, and bee venom. Additionally, honeybee farming can provide indirect benefits related to forest resource conservation and increased crop productivity through the mutually beneficial symbiosis between plants and honeybees, as honeybees aid in the pollination of plant flowers while foraging for food. My Bee Kelulut is a partner in this community service activity, which involves the cultivation of Trigona bees, a type of stingless bee, that has been carried out since 2017 by several students from the Forestry Department of the Faculty of Agriculture at the University of Palangka Raya at the Campus Forest Seedling Nursery. The implementation of the Community Entrepreneurship Mentor Program (PDPWM) has resulted in a new product, My Bee Kelulut Bee Pollen, packaged in bottles and ready for market